Pengaruh Kombinasi Pemberian Infrared Dan William Flexion Exercise Terhadap Peningkatan Fungsional Pada Pasien Nyeri Punggung Bawah - Nurul Halimah; Angria Pradita; Vivin Aini Zahroh Usmawanti; Duwi Ana Tiara Tiara (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: To identify the effect of infrared therapy and William's flexion exercises on functional improvement in low back pain patients at the physiomar clinic. Methods: This article uses an experimental research design with a one pre test – protest control group design, namely giving intervention to one group to see the difference before and after giving the intervention. The study population was all patients at the physiomar clinic who met the characteristics of the respondents, namely patients with complaints of low back pain at the physiomar clinic. The sample selection in this study used a purposive sampling technique, namely the technique of determining the sample with certain consideretions according to the inclusion and exclusion criteria.Results: Comparision of functional ability before and after administration of IR and William Flexion showed a significance value of 0,000 (p<0,005) that there was a significant difference in functional abilty between before and after administration of IR and William Flexion.Conclusion: Based on the results of the study, it was concluded that 40 patients (100%) with complaints of non- specifik low back pain by giving infrared physiotherapy modalities combined with providing William Flexion exercises can reduce pain, increase muscle flexibility and restore activity functional.